Protective effects of Zingiber zerumbet ethyl acetate extract on hydrogen peroxide-induced damage of red blood cells - Mohd Fuad Rahmat Sam,; Asmah Hamid,; Ahmad Rohi Ghazali,; Santhana Raj Louis,; Siti Balkis Budin, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Zingiber zerumbet is widely used as therapeutic agent in traditional medicine and is reported to exert antioxidant activities. This study evaluated in vitro antioxidant potential of Z. zerumbet rhizome ethyl acetate extract on hydrogen peroxide (H2O2)-induced red blood cells (RBCs) damage; by measuring percentage of haemolysis, oxidative damage and morphological changes in treated RBCs. On a preliminary dose-response analysis, it was observed that incubation of RBCs with extract at doses of 50, 25, 12.5 and 6.25 μg/mL all had no significant effect on RBCs similar to NaCl control and BHT (positive control), therefore, these concentrations were used in the subsequent study. The RBCs were pre-incubated with extract in the chosen concentrations, prior to treatment with H2O2. The results showed that only 6.25 μg/mL+H2O2 group showed significantly (p<0.05) lower percentage of haemolysis and oxidative damage; indicated by low level of malondialdehyde (MDA) and protein carbonyls (PC) compared to the H2O2 alone group. Electron microscopic examination further showed that pre-treatment with 6.25 μg/mL extract reduced the H2O2 –induced morphological changes of RBCs. Phytochemical analysis of extract using Gas Chromatography Mass Spectrometry (GCMS) identified Zerumbone as the highest constituent compound (51.57%) in this extract. In conclusion, this study indicated that 6.25 μg/mL ethyl acetate extract Z. zerumbet rhizome could efficiently protect RBCs against oxidative damage induced by H2O2 and this effects could possibly due the high constituent of Zerumbone.